Training on the Development of Chemical Multiple Representations Integrated PowerPoint-iSpring Learning Media: a case of Chemistry Teachers in Padang - Guspatni Guspatni; Budhi Oktavia; Fajriah Azra; Minda Azhar (Fakultas MIPA Universitas Negeri Padang, 2022)
The training